Effect of seed damage on growth and development in pea (Pisum sativum L.) and wheat (Triticum aestivum L.) - Chin, H. F.; Aitken, Yvonne (Oxford University Press, 1976)
The effect of damage to the food storage of the seed on the ensuing plant was compared in cultivars of two species differing in seed structure, the Greenfest pea with cotyledons and the Gabo wheat with endosperm. Partial removal of storage tissue slightly retarded growth rate in both species and slowed development rate in sheat. Complete removal lowered the germination rate, drastically slowed the growth rate of the survivors for the first 20 d after sowing and lowered the development rate throughout the life cycle. This treatment doubled teh time to flower initiation (20 d later) compared with the control, thus indicating the promotive role of both cotyledon and endosperm in the progress of the shoot towards the reproductive state. The number of vegetative nodes in the pea was lowered by two nodes whereas it was raised by one in the wheat